2011
DOI: 10.1093/geront/gnr033
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Chinese American Elders into Dementia Research: The UCSF ADRC Experience

Abstract: Despite the significant cultural and linguistic barriers, Chinese Americans can be successfully recruited into longitudinal studies of aging and cognitive impairment. Clinical services are a critical component of such an effort, and low education and other factors that may be associated with it are clear barriers to research participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 21 publications
(19 reference statements)
2
70
0
Order By: Relevance
“…Unlike our study, Davis et al (2002) found that the implementation of multiple follow-up strategies was the most important factor in achieving high retention rates regardless of the population being studied. Our findings that relationships, including elements of trust, cultural competence, and participants’ wariness of financial conflicts of interest, are crucial to participant retention are consistent with previous studies that found these to be important factors in peoples’ willingness to enroll in research (Chao et al, 2011; Dilworth-Anderson, 2011; Kirkby, Calvert, Draper, Keeley, & Wilson, 2012; Manson, Garroutte, Goins, & Henderson, 2004). A focus group study with African American research participants found that a lack of trust in scientific research, academic institutions, and researchers themselves, as well as the failure of researchers to share their findings with the community, were participation barriers regardless of SES or education (Williams et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Unlike our study, Davis et al (2002) found that the implementation of multiple follow-up strategies was the most important factor in achieving high retention rates regardless of the population being studied. Our findings that relationships, including elements of trust, cultural competence, and participants’ wariness of financial conflicts of interest, are crucial to participant retention are consistent with previous studies that found these to be important factors in peoples’ willingness to enroll in research (Chao et al, 2011; Dilworth-Anderson, 2011; Kirkby, Calvert, Draper, Keeley, & Wilson, 2012; Manson, Garroutte, Goins, & Henderson, 2004). A focus group study with African American research participants found that a lack of trust in scientific research, academic institutions, and researchers themselves, as well as the failure of researchers to share their findings with the community, were participation barriers regardless of SES or education (Williams et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…27,31-34 Overcoming barriers, such as lack of awareness or understanding about research and historical mistrust of the research community, requires a sustained effort. Yet researchers are typically funded on a trial-by-trial basis and may not have the resources needed to build sustained relationships and infrastructure with the community.…”
Section: Awareness Outreach Building Trustmentioning
confidence: 99%
“…As part of its outreach efforts, the UCSF MAC maintains two outreach clinic sites in San Francisco’s Chinatown where Chinese-speaking patients can be referred for cognitive evaluation (16). In addition, patients from the regular MAC cognitive assessment clinic at UCSF are recruited into the ADRC, and some patients are self-referred or referred by other practitioners directly into our research studies.…”
Section: Methodsmentioning
confidence: 99%